False-positive troponin I elevation in a newborn with neonatal encephalopathy. Issue 5 (22nd May 2019) - Caredda, Elisabetta; Rosso, Roberto; Capristo, Carlo; Montaldo, Paolo
Abstract : Serum biomarkers of myocardial damage are commonly used in babies after perinatal asphyxia. We present a case report of a persistently troponin I elevation without evidence of clinical or instrumental signs of myocardial ischaemia in a baby with perinatal asphyxia. When the blood was mixed with polyethylene glycol we found that the troponin I levels were falsely elevated due to interfering antibodies. This case shows that analytical errors may still occur despite modern immunoassay systems and underlines the need for further investigations to identify false-positive values in case of disagreement between clinical conditions and laboratory values.